(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to measure financial performance and its effect on the level of credit risk. Financial performance used to predict credit risk consists of the level of capital adequacy measured through the Capital Adequacy Ratio (CAR) and the amount of credit measured through a Loan to Deposit Ratio (LDR), while credit risk is measured through the level of non-performing loans (NPLs). The research method uses descriptive and verificative methods. The research was conducted on commercial banks listed on the IDX during the period of 2014-2018. Observations were made on 35 commercial banks through the purposive sampling method. Data analysis using panel data regression models by testing as required. The results showed that the Capital Adequacy Ratio (CAR) has a significant effect on credit risk (NPLs), while the Loan to Deposit Ratio (LDR) has no significant effect on credit risk (NPLs).